Penentuan Waktu Pernikahan Perspektif ‘Urf (Study Kasus di Desa Wedi Kecamatan Kapas Kabupaten Bojonegoro) - Hasbi Ash Shiddiqi; M. Rizqi Alfian Rizal (Student Research Journal, 2023)
Marriage is a religious call that must be carried out by humans for those who can afford to have a family. Everyone who wants to get married definitely wants smoothness in the procession of the marriage contract and smoothness in their household life. In this case the authors took samples in Wedi Village, Kapas District, Bojonegoro Regency. For some people in Wedi Village, the use of weton calculations in marriage is mandatory.The main question to be answered in this research is: How is the practice of determining the time of marriage in Wedi Village, Kapas District, Bojonegoro Regency, 'Urf Perspective?To answer this question, this research uses a normative juridical approach, where this research is often called doctrinal research, where the data used are secondary data sources. The process starts from the premises in the form of known positive legal norms and ends with the discovery of legal principles which are the starting point for the search for positive legal norms. Or in short, the method of normative juridical approach is an approach that examines secondary data in the field of law that exist as library data. Based on the results of research in the field, the practice of marriage in Wedi Village, Kapas District, Bojonegoro Regency is to use the weton calculation to determine whether the two prospective brides are matched or not. If based on the results of the weton calculation it turns out that they are matched, then the next step is to determine the day, date, month and hour of the contract also using the weton calculation. The factors behind the practice of determining and calculating the time for marriage in Wedi Village, Kapas District, Bojonegoro Regency are the reasons for not violating religious teachings, the reasons for customary calls, reasons for obligations and considerations of neptu, safety reasons, reasons for events that have occurred and reasons for preservation to generations. The custom that has been formed so far turns out to be in accordance with and absorbed by the rules of 'Urf. Thus, this shows that the determination of the wedding day in Wedi Village, Kapas District, Bojonegoro Regency is 'Urf valid.